Clinical assessment of gastric emptying and sensory function utilizing gamma scintigraphy: Establishment of reference intervals for the liquid and solid components of the Nottingham test meal in healthy subjects. Issue 11 (6th June 2017) - Parker, H. L.; Tucker, E.; Blackshaw, E.; Hoad, C. L.; Marciani, L.; Perkins, A.; Menne, D.; Fox, M.
Abstract: Background: Current investigations of stomach function are based on small test meals that do not reliably induce symptoms and analysis techniques that rarely detect clinically relevant dysfunction. This study presents the reference intervals of the modular "Nottingham test meal" (NTM) for assessment of gastric function by gamma scintigraphy (GSc) in a representative population of healthy volunteers (HVs) stratified for age and sex. Methods: The NTM comprises 400 mL liquid nutrient (0.75 kcal/mL) and an optional solid component (12 solid agar‐beads (0 kcal). Filling and dyspeptic sensations were documented by 100 mm visual analogue scale (VAS). Gamma scintigraphy parameters that describe early and late phase Gastric emptying (GE) were calculated from validated models. Key Results: Gastric emptying (GE) of the liquid component was measured in 73 HVs (male 34; aged 45±20). The NTM produced normal postprandial fullness (VAS ≥30 in 41/74 subjects). Dyspeptic symptoms were rare (VAS ≥30 in 2/74 subjects). Gastric emptying half‐time with the Liquid‐ and Solid‐component ‐NTM was median 44 (95% reference interval 28‐78) minutes and 162 (144‐193) minutes, respectively. Gastric accommodation was assessed by the ratio of the liquid‐NTM retained in the proximal:total stomach and by Early phase emptying assessed by gastric volume after completing the meal (GCV0). No consistent effect of anthropometric measures on GE parameters was present. Conclusions and Inferences: Reference intervals are presented for GSc measurements of gastric motor and sensory function assessed by the NTM. Studies involving patients are required to determine whether the reference interval range offers optimal diagnostic sensitivity and specificity. Abstract : Failure of current investigations to explain the causes of dyspeptic symptoms may be related to small test meals and analysis techniques that rarely detect clinically relevant symptoms. This study provides reference intervals for gastric motor and sensory function by gastric scintigraphy for the large liquid/solid Nottingham test meal (NTM). The NTM is well tolerated and suitable for use in clinical practice.